(untitled) (Global Scientific Review, 2022)
The world produces different types of gasoline. They can be divided into three levels. The first level includes permanent ordinary gasoline. It has the recommended properties in terms of 90-92 octane number according to the research method and the amount of sulfur, aromatic hydrocarbons, benzene and olefins in a certain area and it will have an octane rating of at least 95 and the characteristics that define the area to be produced, and finally the third tier will include Super gasoline. This includes the requirements for the octane number of gasoline to be not less than 98 and the content of sulfur, aromatic hydrocarbons, benzene and olefins